Jujube in Malay medical manuscript: a comparison from scientific and Islamic perspectives - Mohamad Sabri, Najihah; Tukiran, Nur Azira; Roslan, Raihanah (UKM Press, 2024)
Jujube known as ‘Bidara’ in Malay customs is a beneficial plant to humans. Nowadays, it is being domestically produced into varieties of products to fulfill human needs. However, as time passed, Jujube was only seen as a source for business products while ignoring its real benefits. Thus, this paper aimed to illustrate its benefits as stated in the transliterated books of Malay medical manuscripts, with solid support from scientific and Islamic perspectives. As a common ingredient for remedies, jujube has been documented in old manuscripts such as Kitab Tib MSS 2151, Kitab Tib Muzium Terengganu, The Medical Book of Malayan Medicine, and Kitab Al-Rahmah Fi al-Tibb Wa Al-Hikmah. Past journals and articles were analyzed to describe the benefits of jujube from scientific and Islamic points of view which are derived from the Quran and Hadith. In the selected Malay medical manuscripts, jujube was prescribed as a remedy for dysentery, loss of appetite, sore throat, smallpox, and scorpion sting. Scientific findings have broadened the discoveries of its medicinal advantages with the presence of properties such as anti-diarrheal, antimicrobial, anti-inflammatory, antidiabetic, antioxidant, anticancer, and antiallergic. Islamic views which are derived from the Quran, Hadith, and scholars’ books mainly circulate its benefits as a cleansing agent, black magic defense mechanism, and medicine for certain illnesses. To conclude, this paper will review the benefits of jujube from the ancient Malay medical manuscript, which is parallel with the Islamic perspective and supported by scientific findings.